2016
DOI: 10.1039/c6ce00115g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and formation mechanisms of morphology-controllable indium-containing precursors and optical properties of the derived In2O3 particles

Abstract: Indium-containing precursors with three morphologies were synthesized, and the formation mechanisms were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…3 c. The spacing with 0.248 nm is consistent with the inter-planar spacing of the (002) planes of hexagonal ZnO phase [ 12 ]. The left part clearly exhibits the In 2 O 3 (222) facets with a spacing value of 0.285 nm, which is consistent with the reported value [ 24 ]. The good crystalline quality and the sharp interface between ZnO and In 2 O 3 would be advantageous for the separation of the photo-generated charge carriers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3 c. The spacing with 0.248 nm is consistent with the inter-planar spacing of the (002) planes of hexagonal ZnO phase [ 12 ]. The left part clearly exhibits the In 2 O 3 (222) facets with a spacing value of 0.285 nm, which is consistent with the reported value [ 24 ]. The good crystalline quality and the sharp interface between ZnO and In 2 O 3 would be advantageous for the separation of the photo-generated charge carriers.…”
Section: Resultssupporting
confidence: 91%
“…In 2 O 3 with a band gap of 2.56 eV has been proved as efficient sensitizer to extent the light absorption spectra by coupling other semiconductor. Also, its valence and conduction band alignments are staggered relative to those of ZnO [ 24 , 25 ]. A lot of researches on In 2 O 3 -ZnO composite have been reported for degradation of organic compounds and hydrogen production by photocatalysis [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 On the other hand, PLE spectroscopy has been used as a technique to measure the absorption edge of semiconductor materials. 33,34 Figure 8 plots the PL and PLE spectra of the as-grown In 2 O 3 films grown on (100), (110), and (111) YSZ substrates. The excitation wavelength of 400 nm was used for the PL spectra measurements, and the PL peak appeared at ∼2.16 eV (575 nm), which is consistent with the greenish-yellow appearance of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Various morphologies of In 2 O 3 have been synthesized, such as nanorods, nanocubes, nanowires, nanosheets, nanobelts, nanoparticles, nanobers, corundum-type nanotubes and ower like In 2 O 3 etc. [6][7][8][9][10][11][12][13][14][15] It has been reported that tunability of micro/nanosized In 2 O 3 structure can induce emission in different wavelength ranging from ultraviolet (UV) to visible region. 16 For example, Cao and co-workers synthesized In 2 O 3 nanowires and observed intense ultraviolet emission.…”
Section: Introductionmentioning
confidence: 99%